Characteristic of tropical storm pabuk based on field measurement - Shamsudin, M.A. (Offshore Technology Conference, 2020)
Tropical Storm (TS) Pabuk which occurred in South China Sea during the Northwest Monsoon season of 2018-2019 is a rare storm event. Even though it was originally considered weak, it was able to enter and remains active in the 5 degree latitude of weak Coriolis zone, then track further north, make a short land crossing before ending in Andaman Sea. At its early formation, it was in tune with the incoming monsoon's cold surge which perfectly align with the storm outer circulation that enable it to amplify like a little push that spun a spin-top going faster. The waves measured during this storm far exceeds the waves conditions associated with a 100 year Return Period (RP). In addition to being larger, they are also much steeper than the waves contained in the SEAFINE hindcast database spanning back over the past 59 years. However, interestingly, correlating the generated waves with the local wind field showed that at the locations where the data originated, the peaks in wave conditions are contributed by swell. Copyright 2020, Offshore Technology Conference